Effects of transcranial magnetic stimulation on cerebellar ataxia: A systematic review and meta-analysis - Wang, Ying; Zhang, Di; Wang, Ju; Ma, Jiang; Lu, Li; Jin, Song (Frontiers in Neurology, 2023)
Objective To determine the effectiveness of transcranial magnetic stimulation in improving cerebellar ataxia. Data sources PubMed, EMBASE, the Cochrane Library, Springer, Science Direct, the China National Knowledge Infrastructure (CNKI) and the China Science and Technology Journal Database (VIP) were searched until 2022. Review methods Trials with transcranial magnetic stimulation on the effects on cerebellar ataxia were included, and the effect size was evaluated using the standardized mean difference (SMD) or mean difference (MD) and a 95% confidence interval (CI). Results Eight studies comprising 272 participants, published between 2014 and 2022, were included. The results revealed that the effect of TMS on patients with cerebellar ataxia as assessed by the International Cooperative Ataxia Rating Scale (ICRAS), the Scale for the Assessment and Rating of Ataxia (SARA), the Berg Balance Scale (BBS), and the Timed Up and Go (TUG) test was statistically significant (P < 0.01) with low heterogeneity among the studies (I2 = 4, 27, 0, and 0% respectively). Conclusion The effects of transcranial magnetic stimulation in improving cerebellar ataxia in the affected patients are significant. TMS targeting the cerebellar structures can induce changes in the excitability of the cerebellar-thalamus-cortical pathways; thus, it is necessary to carry out large-scale research with good design and high quality in the future.